2008
DOI: 10.1186/1752-0509-2-1
|View full text |Cite
|
Sign up to set email alerts
|

A simple principle concerning the robustness of protein complex activity to changes in gene expression

Abstract: Background: The functions of a eukaryotic cell are largely performed by multi-subunit protein complexes that act as molecular machines or information processing modules in cellular networks. An important problem in systems biology is to understand how, in general, these molecular machines respond to perturbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
96
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 24 publications
7
96
0
Order By: Relevance
“…Following polyploidization, balanced gene loss operates to maintain equitable dosage among functionally related loci participating in protein complexes. Similarly, studies in yeast have revealed that dosagesensitive genes are more likely to encode subunits of protein complexes (4,52), further indicating the strong selective pressure to maintain the stoichiometric interdependence of multiple gene products that form a single functioning macromolecule (43). In humans, dosage imbalance of interacting proteins has been hypothesized to predispose to disease (53).…”
Section: Discussionmentioning
confidence: 99%
“…Following polyploidization, balanced gene loss operates to maintain equitable dosage among functionally related loci participating in protein complexes. Similarly, studies in yeast have revealed that dosagesensitive genes are more likely to encode subunits of protein complexes (4,52), further indicating the strong selective pressure to maintain the stoichiometric interdependence of multiple gene products that form a single functioning macromolecule (43). In humans, dosage imbalance of interacting proteins has been hypothesized to predispose to disease (53).…”
Section: Discussionmentioning
confidence: 99%
“…A potentially relevant point is that proteins with oligomerization potential can also be costly, providing the substrate for well-known human disorders involving inappropriate protein aggregates (e.g., Alzheimer’s and Parkinson’s diseases) (16), and more generally encouraging deleterious promiscuous protein-protein interactions when overexpressed (99, 104). This fine line between adaptive complexity and pathology encourages the hypothesis that the evolutionary roots of numerous protein-protein interactions may simply reside in their initial roles as compensating mechanisms for mild structural defects of monomeric proteins (25).…”
Section: Protein Structure and Complex Cellular Adaptationsmentioning
confidence: 99%
“…Second, unless a newly emerging dimer has a symmetric interface and the correct subunit orientation, concatenations into indefinite filaments can arise. Numerous human disorders are known to result from inappropriate protein aggregation (11), and highly expressed proteins are especially vulnerable to promiscuous interactions (12,13). Third, in diploid species, some dimerizing mutations may have deleterious effects in heterozygous individuals as a consequence of heterotypic complexation, a process that can greatly reduce the probability of establishment of the dimerizing allele (10).…”
mentioning
confidence: 99%